GENETIC DIVERSITY OF Dendrocalamus asper IN JAVA REVEALED BY RAPD MARKERS - Rimbawanto, Anto (Indonesian Journal of Forestry Research, 2006)
Dendracalamusasper is  one of  the most widely use and widely distributed bamboo  species in Indonesia. A genetic conservation plot has been established to maintain genetic diversity of the species. A total of  115 samples  were collected from 12 sites throughout Java. Genetic diversity was revealed using 31   RAPD  primers  producing  64 polymorphic  bands.  A total  of  81  different  multi-locus genotypes (genets) were identified between 115 samples. TI1e total number of multi-locus genotypes in all populations ranged from 3 to 9 (mean 6.5),  indicating that all populations consisted of multiple genotypes. Mean genetic diversity was 0.04, (ranging from the lowest 0.009 in Kuningan population to the highest 0.144  in Purwokerto population). The Simpsons diversity index indicated  that the most population composed of  unique genotype. Geographical differences did not correlate with genetic cluster.